(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed at identifying the comparative training and its effect on the trajectory and achievement among young weightlifters. It employed the experimental approach to verify research hypotheses. The research sample consisted of (24) players representing the Iskan Youth Club in Iraq and the Iranian Shomal Club. The players were randomly divided into two groups (experimental and control). They underwent the processes of homogeneity and equality with their pre-measurements including height, age and the relative achievement of the snatch. The coach method was adapted with introducing training units corresponding to their counterpart Iranian Shomal Club. The data was processed statistically. The results revealed that the comparative training helps to shorten the duration of training because of its specificity by matching the variables of the two samples.